Pengaruh Warna Dan Bentuk Lampu Terhadap Tingkat Kenyamanan Manusia Di Ruang Tidur - Anisa Furtakhul Janah; Upik Nurbaiti; Fianti Fianti (Universitas Lambung Mangkurat, 2020)
The purpose of this study was to study the effect of various light colors and shape on light intensity and visual contentment levels. This research was experimental research consisting of two variables consisting of light colors with four colors: red, yellow, green, and blue, and three different lamp shapes: round, spiral, and essential. The lamp used for color variations had a power of 2.5 watts, while the lamp used for variations in shape had a power of 5 watts. The parameters studied in this study were the lighting and the light intensity produced. The data analysis technique used in this study contained the value of light intensity and the percentage of visual contentment levels obtained from the questionnaire results. The results showed that the yellow light had the highest light intensity of 40 CDs, this result was supported by a questionnaire that showed the contentment level of respondents in the bedroom using a yellow light was 70%. Round lights have the highest intensity because they did not produce a luminous effect, thus producing very little lamp energy waste.